The Development of National Beef-Cattle Population in Relation to Beef-Cattle Population at the Centre and Non Centre Area, and the Policy of National Development Program - Sodiq, A; Nurwakhidati, yusuf (ANIMAL PRODUCTION, 2006)
The objectives of this research were (1) to find out the development of beef-cattle population at national level, at the Centre Area of Population (CAP) and Non Centre Area of Population (NCAP), (2) to assess the relation between population of national beef-cattle and beef-cattle population at CAP and NCAP, (3) to study the policy of beef-cattle development program in Indonesia. The target of this study addressed to the Directorate General of Livestock Services, Republic of Indonesia. A literature review and communication methods were applied in this study. Descriptive and regression analysis were used for data analysis.  The study revealed that: (1) During 1995-2005, beef-cattle population at national level, CAP and NCAP were unstable.  Due to financial crises (1997), the population at national and CAP tended to decrease, but the population at NCAP was relatively constant.  During 2003-2005, national population tended to increase (0.83% per year), and that figure was less than national target (1.05%),  (2) Population of national beef-cattle (Y) was highly related (r2: 0,95; MSE: 108508) to the population of beef-cattle at NCAP (X);  Y = 4764492 + 0.896 X;  (3) An increase in beef-cattle population during 2000-2005 was due to an increase in calving and cattle importation. Slaughtering of cows should be controlled to increase calving. The evaluation results of beef self-sufficiency program revealed that there were failures in achieving main goals of the program. It is recommended that to improve the contribution of CAP to national needs, the development of cattle population should be focused in those areas.  The evaluation results of beef self-sufficiency program could be considered in the future policy in term of the development cattle population. Some causes of the policy failures: (1) the formulated policy was not equipped with detailed operation plans. The program formulation was limited to title and goal without elaborating the way to achieve the goal; (2) the programs prepared by the government were on national level with top down approaches but only at small scale considering the goal that were going to be achieved; (3) With only one common implementation strategy without considering the regional potential but based on prime commodity instead. Therefore, the program were scattered in very small sizes; and (4) The programs implementation were not carried out with methods that can be evaluated whether they were achieved or not and the program can not be adjusted to suit the local conditions. (Animal Production 8(3): 182-189 (2006) Key Words: Indonesia, beef-cattle population, beef-cattle development program